Analysis of Media Outlets on Women's Health: Thematic and Quantitative Analyses Using Twitter - Alvarez-Mon, Miguel A.; Donat-Vargas, Carolina; Llavero-Valero, Maria; Gea, Alfredo; Alvarez-Mon, Melchor; Martinez-Gonzalez, Miguel A.; Lopez-del Burgo, Cristina (Frontiers in Public Health, 2021)
Background: Media outlets influence social attitudes toward health habits. Analysis of tweets has become a tool for health research. Objective: The objective of this study was to investigate the distribution of tweets about women´s health and the interest generated among Twitter users. Methods: We investigated tweets posted by 25 major U.S. media outlets about pre-menopausal and post-menopausal women´s health between January 2009 and December 2019 as well as the retweets generated. In addition, we measured the sentiment analysis of these tweets as well as their potential dissemination. Results: A total of 376 tweets were analyzed. Pre-menopausal women´s health accounted for most of the tweets (75.3%). Contraception was the main focus of the tweets, while a very limited number were related to infertility (1.4%). With regards to medical content, the effectiveness of contraceptive methods was the most frequent topic (46.2%). However, tweets related to side effects achieved the highest retweet-to-tweet ratio (70.3). The analysis of sentiments showed negative perceptions on tubal ligation. Conclusions: The U.S. media outlets analyzed are more interested in pre-menopausal than in post-menopausal women health and focused their content on contraception, while Twitter users showed greater interest in side effects.